The "Saúde na Boa" project in promoting a healthy lifestyle among high school students - Maria Alice Altenburg Assis; Markus Vinícius Nahas; Mauro Virgílio Gomes Barros (Universidade Federal de Santa Catarina, 2014)
The "Saúde na Boa" project in promoting a healthy lifestyle among high school students